Co-60 gamma irradiation prevents Bothrops jararacussu venom neurotoxicity and myotoxicity in isolated mouse neuromuscular junction - Souza, FAD; Spencer, P. J.; Rogero, JR; Nascimento, N.; Dal Pai-Silva, M.; Gallacci, M. (Elsevier B.V., 2002)
The ability of gamma radiation from Co-60 (2000 Gy) to attenuate the toxic effects of Bothrops jararacussu venom was investigated on mouse neuromuscular preparations in vitro. A comparative study between the effects of native and irradiated venoms was performed on both phrenic-diaphragm (PD) and extensor digitorum longus (EDL) preparations by means of myographic, biochemical and morphological techniques. Native venom (10 and 20 mug/ml) induced a concentration-dependent paralysis of both directly and indirectly evoked contractions on PD preparations. At 20 mug/ml, it also caused a pronounced myotoxic effect on the EDL muscle preparation that was characterized by an increase of creatine kinase release and by several morphological changes of this preparation. By contrast, irradiated venom, even at concentrations as high as 40 mug/ml, induced neither paralyzing nor myotoxic effects. It was concluded that Co-60 gamma radiation is able to abolish both the paralyzing and the myotoxic effects of B. jararacussu venom on the mouse neuromuscular junction. These findings support the hypothesis that gamma radiation could be an important toot to improve antisera production by reducing toxicity while preserving immunogenicity. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: gamma radiation; Bothrops jararacussu venom; neuromuscular junction